2017
DOI: 10.1007/s10811-017-1290-4
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris (SAG 211-12) biofilm formation capacity and proposal of a rotating flat plate photobioreactor for more sustainable biomass production

Abstract: Difficulties and cost of suspended microalgal biomass harvest and processing can be overcome by cultivating microalgae as biofilms. In the present work, a new photoautotrophic biofilm photobioreactor, the rotating flat plate photobioreactor (RFPPB), was developed aiming at a costeffective production of Chlorella vulgaris (SAG 211-12), a strain not frequently referred in the literature but promising for biofuel production. Protocols were developed for evaluating initial adhesion to different materials and testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Various supporting matrices have been trialled for algal biofilm wastewater treatment processes - Adey et al (1993) reported highest microalgae productivity (15-27g/m 2 .d) when treating agricultural run-off wastewater with biomass attached to plastic screens -while Zhuang et al (2018) found that cotton, polycarbonate and cellulose acetate were the most commonly used supports. Melo et al (2018) tested borosilicate glass, polyurethane foam, polyvinyl chloride, stainless steel, polyethylene and polypropylene, reporting that PVC was the most appropriate for culturing C. vulgaris on a rotating flat plate photobioreactor (RFPPB).…”
Section: Advantages Of Attached Growth Communitiesmentioning
confidence: 99%
“…Various supporting matrices have been trialled for algal biofilm wastewater treatment processes - Adey et al (1993) reported highest microalgae productivity (15-27g/m 2 .d) when treating agricultural run-off wastewater with biomass attached to plastic screens -while Zhuang et al (2018) found that cotton, polycarbonate and cellulose acetate were the most commonly used supports. Melo et al (2018) tested borosilicate glass, polyurethane foam, polyvinyl chloride, stainless steel, polyethylene and polypropylene, reporting that PVC was the most appropriate for culturing C. vulgaris on a rotating flat plate photobioreactor (RFPPB).…”
Section: Advantages Of Attached Growth Communitiesmentioning
confidence: 99%
“…Pasteurization of the reactors was carried out using a Tuttnauer 2840EL-D autoclave (15 min, 121°C). The culture medium was the SAG medium dedicated to the particular species of algae, excluding nitrogen compounds [33,34]. In order to obtain high lipid productivity, a nitrogen regime was used in accordance with the literature [35,36].…”
Section: Algae Species and Culture Conditionsmentioning
confidence: 99%
“…The efficiency of UV-ozone treatment to improve the wettability of polymers was recently also reported for the application of PMMA polymer in chip fabrication. 17 Nevertheless, the severe damages that UV light can cause to PMMAs [40][41][42] were neither taken into consideration nor monitored. Here, the treatment of an aged polymer layer with direct UV irradiation for 2 min in the PULC-120 without the reaction cell did not improve the hydrophilicity.…”
Section: B Polymer Coatingmentioning
confidence: 99%